Exile and Emigration: Tenets of Editorial Galaxia from its Foundation until the 1960’s. The Case of Argentina and Uruguay - Villanueva Gesteira, María Dolores (Madrygal. Revista de Estudios Gallegos, 2015)
Argentine and Uruguay helped to set the Editorial Galaxia project as the main migrant-receiving countries from Galician exile. For two decades, they collaborated with financial support as well as spreading published books. The relationship between “inland Galicia” and “Galicia abroad” was strong; therefore it was possible to perform common actions.